Peluang Bisnis di Era Teknologi dengan Memanfaatkan E-commerce Sebagai Wadah Usaha Bagi PKBM Sahabat Cendikia - Puspita Rama Nopiana; Yuliadi Yuliadi; Putu Rani Susanthi; Asih Purwana Sari; Suratman Suratman (Sejahtera: Jurnal Inspirasi Mengabdi Untuk Negeri, 2024)
This activity is motivated by people's low motivation to open a business due to their low knowledge about the business world, especially in the current era of digitalization. The PKM method used is the lecture method for delivering discussion studies and the discussion method for solving problems and finding solutions that participants are facing. This PKM activity was carried out in Batam City, especially at PKBM Friends of Cendikia. Results of PKM activities. The results of this activity illustrate that participants must learn to rise from old strategies to strategies for utilizing the world of technology in product marketing by using social media and existing e-commerce systems such as Shopee, Lazada, Tokopedia, Bukalapak, Ralali, JD.ID, Blibli , Upwork, Freelancer, etc)